The novel first-line therapy for rett syndrome - Sultan, Wania; Irfan, Hamza; Shariq, Kainat (International Journal of Medicine, 2023)
Rett Syndrome (RTT) is a neurodevelopmental disorder predominantly affecting females and characterized by hyperkinetic movement disorders and related symptoms. At present, the available treatments for RTT primarily focus on managing symptoms and providing supportive care. This article examines the emergence of trofinetide as an innovative therapeutic approach targeting the underlying molecular and synaptic abnormalities associated with RTT. The approval of trofinetide, marketed as DAYBUE™, as the primary treatment for Rett Syndrome by the US Food and Drug Administration (FDA) is based on encouraging outcomes from clinical trials. Ongoing open-label studies are currently underway to evaluate the long-term efficacy and safety of trofinetide in various age groups, thus providing valuable insights into its sustained benefits. These advancements in research, along with other potential treatments under investigation, offer promising prospects for the development of improved and personalized management strategies for individuals with Rett Syndrome.